Products of Toeplitz and Hankel Operators on the Harmonic Bergman Space - Hongyan Guan; Yan Hao (International Journal of Mathematics And its Applications, 2017)
In this paper, we discuss the product problems of Toeplitz operators, small Hankel and big Hankel operators with quasihomogeneous symbols on the harmonic Bergman space of the unit disk.